THE EFFECT OF INCOME, NETWORKING, AND E-COMMERCE ON THE INTEREST TO BE AN ENTREPRENEUR - Shita Lusi Wardhani; Lita Kusumasari (LPPM STIE YKPN Yogyakarta, 2023)
There is a gap between employment and vacant jobs in Indonesia. It is a problem that needs to be solved. The Indonesian government keeps trying to solve the problem by encouraging the youths to be entrepreneurs. The purpose of the study is looking for the affected factors of entrepreneurs. Previous research stated that income was a dominant factor to be an entrepreneur and to create and make company growth, the network was the key while E-commerce could facilitate all business processes to the world. The hypotheses of the research are higher income expectations, networking, and e-commerce positively affect the interest to be entrepreneurs. The research method is multiple regression. Data is collected by distributing questionnaires to 160 college students. The data passed the validity and reliability. The F test result showed that the model passed. R2 stated that 41.9% of the model was explained by variables. The regression result showed that higher income, networking, and e-commerce positively and significantly affected the interest to be entrepreneurs. Based on the result, the variables should be socialized to encourage unemployment to be entrepreneurs